Family Farming’s Contribution in Increasing Household Income and Stunting - Rosnah, Upik S.; Liufeto, Franchy Ch.; Manongga, Stefanus P. (Interdisciplinary Social Studies, 2023)
Background: The incidence of stunting is influenced by various factors, one of which is income in the household, therefore it is necessary to make efforts to increase income, including the family farming business. Aim: This study aims to determine the contribution of family farming businesses in increasing income and the incidence of stunting at the household level. Method: This research is a type of qualitative research, while data collection techniques are carried out by exploring journals and other information relevant to the study. Findings: The results of the study show that the contribution of family farming businesses can increase income, this can have an impact on increasing the ability to buy nutritious food, thereby reducing the risk of stunting at the household level.